2020
DOI: 10.1016/j.chest.2020.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Tocilizumab Treatment for Cytokine Release Syndrome in Hospitalized Patients With Coronavirus Disease 2019

Abstract: BACKGROUND: Tocilizumab, an IL-6 receptor antagonist, can be used to treat cytokine release syndrome (CRS), with observed improvements in a coronavirus disease 2019 (COVID-19) case series. RESEARCH QUESTION: The goal of this study was to determine if tocilizumab benefits patients hospitalized with COVID-19.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
192
1
5

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 199 publications
(225 citation statements)
references
References 27 publications
18
192
1
5
Order By: Relevance
“…Thus, 28 articles included 991 COVID-19 patients underwent tocilizumab administration were included in this study 10,11, . Of the 28 included studies, 7 of which included 377 patients were case-control studies with a control group not using tocilizumab 28,29,32,36,39,40,42 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, 28 articles included 991 COVID-19 patients underwent tocilizumab administration were included in this study 10,11, . Of the 28 included studies, 7 of which included 377 patients were case-control studies with a control group not using tocilizumab 28,29,32,36,39,40,42 .…”
Section: Resultsmentioning
confidence: 99%
“…Data were unavailable for mortality in 3 studies, and a pooled all-cause death rate of 16% (95% CI, 11-22%; I 2 = 67%, P< 0.0001) was reported in 870 patients when treated with tocilizumab. 17 studies 10,11,19,[21][22][23][25][26][27][28][29]31,33,[35][36][37]40 comprising 562 patients were de ned as severe COVID-19 infection, and the pooled ORR of treatment with tocilizumab was 78% (95% CI, 70-85%; I 2 = 65%, P< 0.0001), while pooled ORR in 64 nonsevere infection was 93% (95% CI, 85-98%; I 2 = 0%, P=0.66) ( Figure S2).…”
Section: Impact Of Tocilizumab Treatment On Orr and Mortality Of Covimentioning
confidence: 99%
See 2 more Smart Citations
“…1,3 A recent study in Chest followed IL-6 levels after tocilizumab administration and found an immediate increase followed by a steady decrease but did not differentiate IL-6 levels between survivors and non-survivors. 4 Data from China found patients with rising IL-6 levels greater than 4000 pg/mL perished despite receiving tocilizumab. 5 These IL-6 levels begin to reach those seen in cytokine release syndrome (CRS) following CAR T cell infusion where levels reach a median value of 8,309 pg/mL for grade 4 or 5 CRS.…”
Section: Methodsmentioning
confidence: 99%